32-4p=-5(p-6)

Simple and best practice solution for 32-4p=-5(p-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 32-4p=-5(p-6) equation:


Simplifying
32 + -4p = -5(p + -6)

Reorder the terms:
32 + -4p = -5(-6 + p)
32 + -4p = (-6 * -5 + p * -5)
32 + -4p = (30 + -5p)

Solving
32 + -4p = 30 + -5p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '5p' to each side of the equation.
32 + -4p + 5p = 30 + -5p + 5p

Combine like terms: -4p + 5p = 1p
32 + 1p = 30 + -5p + 5p

Combine like terms: -5p + 5p = 0
32 + 1p = 30 + 0
32 + 1p = 30

Add '-32' to each side of the equation.
32 + -32 + 1p = 30 + -32

Combine like terms: 32 + -32 = 0
0 + 1p = 30 + -32
1p = 30 + -32

Combine like terms: 30 + -32 = -2
1p = -2

Divide each side by '1'.
p = -2

Simplifying
p = -2

See similar equations:

| 2×-2/1 | | -7n-5=79 | | 0=-18.4x^2+24x+3 | | e+96=156 | | y=bx | | 6ln(3x)=48 | | 28x+15y=144 | | 34-6a=6-8(a-2) | | 4*(e^3x-5)=72 | | 10=-42.24x^2+24x+3 | | x+2x-9+3x-4-5x=6(2x-1) | | 9+2.7x=0.7 | | =(12x^6-9x^5)+(3x^4-27x^2) | | 0=-42.24x^2+24x+3 | | 8x+16-24=4x-8 | | 358/598 | | 9x^2(2x-3)-2x+3=0 | | -7-5r+4r=5-r-3r | | 5(2x-11)=-25 | | -3x^2=2(3x-5) | | 7/6=3/h | | 7-5a-6=-5+4+a-7 | | .1=.05+(x-.05) | | 15+m=40 | | 87=3a | | n=-20+6a | | y=5/3x=1 | | 5p^2-23p+24= | | 2p-7/2=-6p | | 10x-20+20=5x-10 | | .13=.16X+.12(1-X) | | 7w-3(4w+8)=-7 |

Equations solver categories